1928
DOI: 10.1021/ja01391a504
|View full text |Cite
|
Sign up to set email alerts
|

The Freezing Point and Density of Pure Hydrogen Peroxide.

Abstract: Vol. 50 by using a thermometer graduated to 0.1°, which was compared with one recently calibrated by the Bureau of Standards. The filled pycnometer was weighed at each temperature and the density, given in Table I, was calculated from these weights. The coeEcient of cubical expansion of Pyrex glass used was that recently obtained by BuEngton and Latimer.3 All weights were reduced to vacuum.No recent determination of the density of bromoform has been made and those in the literature are not in close agreement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1931
1931
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The difficulty is compounded further by the curious property of the crystalline hydrate, H202 • 2H20, to catalyze the decomposition of the peroxide on melting (10). The above quoted datum, -0.89°C, dates back to 1928 (11). Since then, a number of reinvestigations have confirmed that it is too low by nearly half a degree.…”
Section: The Melting Pointmentioning
confidence: 99%
“…The difficulty is compounded further by the curious property of the crystalline hydrate, H202 • 2H20, to catalyze the decomposition of the peroxide on melting (10). The above quoted datum, -0.89°C, dates back to 1928 (11). Since then, a number of reinvestigations have confirmed that it is too low by nearly half a degree.…”
Section: The Melting Pointmentioning
confidence: 99%